Das musikschaffende Subjekt im historischen Wandel : vom Künstler-Ideal zum kreativ-unternehmerischen Selbst - Just, Steffen; Justus Liebig University Giessen (My University, 2014)
This essay examines the historical dimensions of the production of the musicmaking subject. The first part focuses on the modern conditions under which a distinctive concept of the music-making subject as »autonomous artist« could arise. The second part focuses on contemporary subject productions in popular music with a particular interest in one recent model: the music-making subject as »creative-entrepreneurial self«. This model is exemplified by a reading of self-help literature for musicians. By that, I attempt to show how music-making is guided through historical and culturally distinct (self)understandings of the subjects involved.
Keywords: ddc:780